2017
DOI: 10.1002/mame.201600452
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Architecture and Enhanced Thermal Stability of Electrospun Poly(ε‐caprolactone)/Aminopropyl Isobutyl Polyhedral Oligomeric Silsesquioxane Hybrid Fibers

Abstract: Polymer‐based electrospun fibers have been intensively studied as antimicrobial membranes, drug carriers, and energetic materials. Inorganic fillers or small molecules have been routinely added into polymer matrices in order to enhance product functions. However, the electrospinning process is kinetically controlled and solvent rapidly evaporates due to the large surface‐to‐volume ratio of spinning liquid jet. When electrospinning a multicomponent system, complex phase behavior may occur and give rise to inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…These are important in fiber fabrication since the fiber has to undergo high temperature and different environment during manufacture process and practical deployment. [23][24][25] In addition, as it has been reported, polymer optical gain materials generally show strong phase separation when blended with the transparent matrix such as PMMA and PS. This phase separation represents poor compatibility between two materials, which can be induced by temperature, magnetic field, processing method, and even film thickness.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…These are important in fiber fabrication since the fiber has to undergo high temperature and different environment during manufacture process and practical deployment. [23][24][25] In addition, as it has been reported, polymer optical gain materials generally show strong phase separation when blended with the transparent matrix such as PMMA and PS. This phase separation represents poor compatibility between two materials, which can be induced by temperature, magnetic field, processing method, and even film thickness.…”
mentioning
confidence: 82%
“…The thermal stability of the 7F6/PS blend is also improved significantly compared with the thermal stability of pristine 7F6. These are important in fiber fabrication since the fiber has to undergo high temperature and different environment during manufacture process and practical deployment . In addition, as it has been reported, polymer optical gain materials generally show strong phase separation when blended with the transparent matrix such as PMMA and PS.…”
Section: Introductionmentioning
confidence: 99%
“…have been considered as ideal pore generators for reducing the materials' k values. [15,[25][26][27][28][29][30][31][32] Meanwhile, the organic-inorganic hybrid nature and high reactivity of POSSs endow the resulting materials high thermal [28,[32][33][34][35] and mechanical performance, [36,37] large surface area and pore volume, [38][39][40][41] and unique surface properties. [42,43] Recently, we demonstrated that larger POSS (i.e., T 10 and T 12 POSSs) is better nano-building block and filler for fabricating thermally and mechanically robust low-k materials.…”
Section: Introductionmentioning
confidence: 99%